ANALYSIS OF HUMAN RESOURCE MANAGEMENT TOWARDS IMPROVING EMPLOYEE PERFORMANCE MAQHASID SHARIA REVIEW - Abdul Latif Rizqon; Tambusai, Muhamad Kharis; Hastuti, Nurul Dwi; Hidayat, Ahmad Agus (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2023)
Human resource management is the first point that must be considered by the company, the development of a business requires quality human resource management. The purpose of the study is to determine the implementation of human resource management in terms of sharia maqhasid and improve employee performance. The methods used are qualitative research, while the data used in primary and secondary data research are obtained by researchers through observation, interviews, and documentation. The results of research on the application of human resource management have an influence on employee performance, one of which is the results of work. The implementation of human resource management seen from sharia maqhasid is by the review of sharia maqhasid, namely dharuriyyat, hajiyyat, and tahsiniyyat.